Fit for America : Major John L. Griffith and the quest for athletics and fitness - Lindaman, Matthew (Sports and entertainment., 2018)
"Fit for America is about the career of Major John L Griffith in relation to his involvement as a key figure in the promotion and organization of intercollegiate athletics over the first half of the twentieth century"--